1993
DOI: 10.1530/jrf.0.0970133
|View full text |Cite
|
Sign up to set email alerts
|

Stage-dependent modulation of Sertoli cell steroid production in dogfish (Scyliorhinus canicula)

Abstract: Seminiferous lobules of dogfish (Scyliorhinus canicula)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…After the development of a transillumination technique allowing the collection of freshly isolated spermatocytes of S. canicula (Sourdaine and Garnier, 1993; M. LOIR E T AL. Sourdaine and JBgou, 19891, it was possible to demonstrate that total protein secretion was highest from the start of spermiogenesis.…”
Section: Sertoli Cell-germ Cell Interactionsmentioning
confidence: 99%
“…After the development of a transillumination technique allowing the collection of freshly isolated spermatocytes of S. canicula (Sourdaine and Garnier, 1993; M. LOIR E T AL. Sourdaine and JBgou, 19891, it was possible to demonstrate that total protein secretion was highest from the start of spermiogenesis.…”
Section: Sertoli Cell-germ Cell Interactionsmentioning
confidence: 99%
“…With regard to our previous results showing an increase of the testosterone content in testicular zones and in isolated spermatocysts containing late spermatids (Sourdaine et al 1990;Sourdaine and Garnier 1992), it may be possible that this steroid play a role in the synthesis of some polypeptides in cysts with late spermatids as observed in mammals. In fact, Sharpe et al (1992) have recently shown that the synthesis or the secretion of several proteins by rat seminiferous tubules (stages VI-VII) was regulated by testosterone.…”
Section: Id-sds-pa Gementioning
confidence: 74%
“…Thus, three (Callard et al 1985) or four (Sourdaine et al 1990) distinct zones, corresponding to the spermatocysts with spermatogonia (zone A: stages I-VI of Mellinger 1965), with spermatocytes (zone B, stages VII-X), with early spermatids (zone C, stages XI-XII) and with late spermatids (zone D, stages XIII-XVIII), can be microdissected. The testicular tissues can then be directly used for measuring biochemical parameters (Callard et al 1985;Sourdaine et al 1990) or dissociated to obtain isolated spermatocysts (Sourdaine and Jgou 1989;Dubois and Callard 1989;Sourdaine and Garnier 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Immature Sertoli cells do have a limited capacity to metabolize cholesterol and progesterone into androgens, as demonstrated in rats [Hall et al, 1969;Tcholakian and Steinberger, 1978] and in dogfish Scyliorhinus canicula [Sourdaine and Garnier, 1993]. In the immature spotted ray Torpedo marmorata , Sertoli cells already displayed the typical organization of a steroidogenic cell when Leydig cells were still fibroblastic [Prisco et al, 2002].…”
Section: Discussionmentioning
confidence: 99%